Disentangling shifts in the soil microbiome of potatoes infected with Rhizoctonia solani AG 3-PT in two contrasting regions of South Africa - Van der Waals, Jacqueline Elise (University of Pretoria, 2024)
Thesis (PhD (Plant Pathology))--University of Pretoria, 2024.